Forest transitions and rural livelihoods: multiple pathways of smallholder teak expansion in Northern Laos - Newby, Jonathan Craig; Cramb, Rob; Sakanphet, Somphanh (MDPI, 2014)
Smallholder teak (Tectona grandis) plantations have been identified as a potentially valuable component of upland farming systems in northern Laos that can contribute to a “livelihood transition” from subsistence-oriented swidden agriculture to a more commercially-oriented farming system, thereby bringing about a “forest transition” at the landscape scale. In recent years, teak smallholdings have become increasingly prominent in the province of Luang Prabang, especially in villages close to Luang Prabang City. In this paper, we draw on a household survey conducted in five teak-growing villages and case studies of different household types to explore the role that small-scale forestry has played in both livelihood and land-use transitions. Drawing on a classification of forest transitions, we identify three transition pathways that apply in the study villages—the “economic development” pathway, the “smallholder, tree-based, land-use intensification” pathway, and the “state forest policy” pathway. The ability of households to integrate teak into their farming system, manage the woodlots effectively, and maintain ownership until the plantation reaches maturity varies significantly between these pathways. Households with adequate land resources but scarce labor due to the effects of local economic development are better able to establish and hold onto teak woodlots, but less able to adopt beneficial management techniques. Households that are land-constrained are motivated to follow a path of land-used intensification, but need more productive agroforestry systems to sustain incomes over time. Households that are induced to plant teak mainly by land-use policies that threaten to deprive them of their land, struggle to efficiently manage or hold on to their woodlots in the long term. Thus, even when it is smallholders driving the process of forest transition via piecemeal land-use changes, there is potential for resource-poor households to be excluded from the potential livelihood benefits or to be further impoverished by the transition. We argue that interventions to increase smallholder involvement in the forestry sector need to take explicit account of the initial variation in livelihood platforms and in alternative transition pathways at the household scale in order to pursue more inclusive “forest-and-livelihood” transitions in rural areas.